Physiological and Productive Performance Responses of Horro Cows to Shade - Gizaw Kebede; Kanchaana Markvichitr; Somkiert Prasanpanich; Chanvit Vajrabukka (Agriculture and Natural Resources, 2005)
Twenty eight Horro cows were used to determine whether shade influences milk production and composition, days open, some physiological and hormonal traits. Cows grazed on natural pasture predominantly, Cynadon dactylon for about 7 hours/day. During grazing, one of the groups had access to shade where as the other group was not allowed to have any shade including trees. Cows were supplemented with concentrate feed during milking in the morning, evening and after grazing. Data on physiological, productive and reproductive parameters between the two groups were compared. Significant differences were observed in respiration rate, rectal temperature, pulse rate and live weight of cows between the two treatments. But there were no significant differences in average daily milk yield, days open and services per conception. Hence it is suggested that a form of shade should be made available for grazing Horro cows.